Service migration optimization method for resource competition in mobile edge computing scenarios - WANG Haiyan; ZHANG Lin; LUO Jian (Tongxin xuebao)
To tackle the problem of resource competition among service migrations caused by limited edge server resources in mobile edge computing (MEC) scenarios, a service migration optimization method for resource competition based on Lyapunov and game theory (OMRC-LG) was proposed. Considering the system's limited migration costs and the difficulty of predicting trajectories when the number of users was large, the service migration was modeled as an optimization problem with migration cost constraints and used the Lyapunov technique to transform it into an online problem without user trajectory prediction. To alleviate resource competition among users, a distributed method based on game theory was proposed. By sharing user service migration decisions, the method obtained accurate information on available edge server resources and would continuously update these decisions to optimize service migration. Simulation results show that the OMRC-LG method can reduce the average service delay while satisfying the migration cost constraints.